2009
DOI: 10.1016/j.jvs.2009.05.017
|View full text |Cite
|
Sign up to set email alerts
|

The Semmes Weinstein monofilament examination as a screening tool for diabetic peripheral neuropathy

Abstract: There is great variation in the current literature regarding the diagnostic value of SWME as a result of different methodologies. To maximize the diagnostic value of SWME, a three site test involving the plantar aspects of the great toe, the third metatarsal, and the fifth metatarsals should be used. Screening is vital in identifying DPN early, enabling earlier intervention and management to reduce the risk of ulceration and lower extremity amputation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
218
2
7

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 297 publications
(233 citation statements)
references
References 40 publications
6
218
2
7
Order By: Relevance
“…This corroborates our systematic review results: DPN and PVD clinical collection methods seem relatively unimportant (4,15). Although several authors have described the foot pulse palpation to have low sensitivity (16,17), the SWM application procedure does not have consensus (18,19) and the tuning fork has low reliability (19); several studies have shown that these simple methods can be implemented for both community (2,8,15,19,20) and high risk (3, 4) setting diabetic foot screening, independently of the variables collection method.…”
Section: Discussionsupporting
confidence: 86%
“…This corroborates our systematic review results: DPN and PVD clinical collection methods seem relatively unimportant (4,15). Although several authors have described the foot pulse palpation to have low sensitivity (16,17), the SWM application procedure does not have consensus (18,19) and the tuning fork has low reliability (19); several studies have shown that these simple methods can be implemented for both community (2,8,15,19,20) and high risk (3, 4) setting diabetic foot screening, independently of the variables collection method.…”
Section: Discussionsupporting
confidence: 86%
“…[32] One of the five results is a summary of the Semmes-Weinstein monofilament examination, which is by itself a sensitive gage of feet neuropathy, even though more involved. [40] In any test the reflex is found to be either absent, reduced or present, which scores 1, 0.5 or 0, respectively. To obtain the score the points are added up.…”
Section: Diabetic Peripheral Neuropathymentioning
confidence: 98%
“…[41,42] DPN is a serious condition which can cause ulceration of feet that, if cannot be treated, might require amputation of affected lower limb extremities. [40] Testing for DPN is theoretically meaningful as the high BP is generally considered a co-factor of T2DM. It creates a favourable environment for glucose to attach to cell receptors.…”
Section: Diabetic Peripheral Neuropathymentioning
confidence: 99%
“…Light touch sensation was assessed with use of the 5.07 SWM [20], which is generally accepted as an effective, inexpensive, portable, painless, easy to administer, and reliable screening method for assessing touch-pressure sensation in a valid fashion. In fact, the SWM was shown to be more sensitive than the vibration perception threshold in measuring peripheral sensation [21,22]. The tester asked blindfolded participants to indicate by stating the word-now when and where on their foot they sensed the pressure of the monofilament.…”
Section: Outcome Measurementsmentioning
confidence: 99%